Геохімія мікроелементів у породах терикону копальні Межирічанська Львівсько-Волинського кам’яновугільного басейну - Книш, І.; Карабин, В. (Геологія і геохімія горючих копалин, 2010)
Досліджено геохімію порід терикону копальні Межирічанська Львівсько-Волинського кам’яновугільного басейну. Породи представлені аргілітами (78 %), алевролітами (14 %), пісковиками (6 %) та вугіллям (2 %). Вугілля копальні – гумусового типу, збіднене мікроелементами, окрім Молібдену, Плюмбуму та Ітербію. Породи терикону концентрують Молібден та Плюмбум, вміст яких вищий, порівняно з кларком для осадових пелітових порід (глини, аргіліти). З’ясовано парагенетичні асоціації хімічних елементів та інші показники щодо порід терикону. Обґрунтовано високу ймовірність у понадфонових кількостях надходження Плюмбуму і Молібдену в суміжні з териконом породи зони аерації та води р. Рати. Запропоновано відповідні запобіжні заходи для зменшення екологічних ризиків. Studied is geochemistry of rocks of waste pile of Mezhirichanska mine of the LvivVolyn coal basin. Rocks are presented by argillites (78 %), aleurolites (14 %), sandstones (6 %) and coal (2 %). Ash level of mixture of rocks of waste pile hesitates from 41 to 98 % and on the average is 70 %. Middle content of sulphur is 2.5 %. Coal of Mezhirichanska mine is of humus type and it is impoverished by microelements, except molybdenum, plumbum and ytterbium. The rocks of waste pile comparatively with clarke of pelite siltages (clays, argillite) have higher content of molybdenum and plumbum by 71 but 39 % areas of waste pile accordingly. In separate areas content of Y, Mn, Yb, V, Co, Sc, P, Be, Cu exceeds clarke in siltages 5 times. Explored separately burnt out and unburnt rocks assert that burnt out rocks comparatively with unburnt have higher ash level (1.6 times) and concentration of chemical elements 1.4–2.6 times. Clearly, that main reason of concentration of metals in burnt out rocks is an increase of their ash level as a result of burnt down of coal. As a result of factor analysis, we found out the associations of heavy metals in mixture of rocks of waste pile. The paragenic associations of chemical elements and other indices of rocks of waste pile are found out: 1. P, Sr, Mn, Ni, Ba, V, Cu, Zr, Sn, Cr, Zn, Ge, Co, Ash level of rocks; 2. siderite, pyrite, chalcopyrite, argillite; 3. burnt rocks, aleurolite, sandstone; 4. unburnt rock, argillite; 5. coal, Mo, unburnt rocks, pyrite, chalcopyrite. As it was found out by authors, in the rocks of waste pile of Mezhirichanska mine, as a result of factor analysis, that Mo is concentrated within the limits of areas with the promoted content of coal and pyrite in mixture of rocks. Unlike Mo and partly Pb content all other elements explored by us are correlated with ash level of rocks. Area of waste pile, within the limits of which all chemical elements are explored by us, does not exceed safe levels, is 23 %. Subsequent researches in these areas of waste pile must find out content of soluble forms of molybdenum and plumbum. It is also necessary to learn distribution of these chemical elements in a vertical cut. The results of such researches will enable us to make decision in relation to the use of rocks of south-western part of waste pile of Mezhirichanska mine. Grounded is high probability of receipt of plumbum and molybdenum in contiguous with the waste pile of rock of area of aeration and water of the river of Rata in background amounts. The proper measures of reduction of ecological risks are offered. For prevention of credible receipt of these metals in contiguous with the waste pile of rock of area of aeration and in water of the river of Rata it is necessary to enclose a waste pile with a ditch and to fill it with sorbent. Grounded is necessity of subsequent research of waste pile.